2010
DOI: 10.1007/s00024-010-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Seismicity and Earthquake Forecast in Western Nepal Himalaya and its Adjoining Indian Region

Abstract: Precursory swarms associated with major earthquakes in the Western Nepal Himalaya and its adjoining region (bounded by 28.0°-31.0°N and 79.5°-82.2°E) have been studied using seismicity data from 1963 to 2006. The delineation of preparation zones for future seismic disturbances is carried out using the temporal and the spatial distribution of earthquakes, considering the events with cutoff magnitude m b C 4.3 in four anomalous episodes: normal/background (N); anomalous/swarm (A); precursory gap (G) and main sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…Dengan menggunakan solusi regresi linier berbobot, parameter model (m 1 dan m 2 ) dapat diselesaikan dengan persamaan: Singh [19] juga meneliti pola atau karakteristik kegempaan sebelum terjadi gempabumi signifikan di daerah Barat Nepal, India. Berdasarkan hasil penelitian ini, karakteristik kegempaan di wilayah Nepal terdapat pola yang menarik yaitu selalu diikuti dengan siklus kegempaan yang terdiri dari siklus normal (N), anomali seismisitas atau peningkatan aktivitas seismisitas (swarm) (A), penurunan aktivitas seismik (precursory gap) (G), dan diikuti gempabumi utama.…”
Section: B Teori Tentang Regresi Model Perkiraan Magnitudounclassified
See 2 more Smart Citations
“…Dengan menggunakan solusi regresi linier berbobot, parameter model (m 1 dan m 2 ) dapat diselesaikan dengan persamaan: Singh [19] juga meneliti pola atau karakteristik kegempaan sebelum terjadi gempabumi signifikan di daerah Barat Nepal, India. Berdasarkan hasil penelitian ini, karakteristik kegempaan di wilayah Nepal terdapat pola yang menarik yaitu selalu diikuti dengan siklus kegempaan yang terdiri dari siklus normal (N), anomali seismisitas atau peningkatan aktivitas seismisitas (swarm) (A), penurunan aktivitas seismik (precursory gap) (G), dan diikuti gempabumi utama.…”
Section: B Teori Tentang Regresi Model Perkiraan Magnitudounclassified
“…Artinya dugaan besarnya magnitudo gempabumi utama bisa dihitung jika siklus kegempaan pada periode swarm telah dilewati sebelum terjadinya gempabumi utama. Menurut Singh [19] kondisi ini hanya berlaku jika pada masa siklus senyap atau penurunan aktivitas kegempaan tidak ada gempabumi dengan magnitudo lebih besar atau sama dengan magnitudo M p . Dengan adanya magnitudo yang lebih besar atau sama dengan M p pada saat periode precursory gap berarti akan mengurangi akumulasi stress pada patahan.…”
Section: Regresi Formula Perkiraan Magnitudo Gempabumi DI Wilayah Benunclassified
See 1 more Smart Citation
“…This is an indication that a possibly wider area will be placed at risk and revised estimates for magnitude and time of occurrence of the main shock may be necessary. Several authors (Bufe et al, 1977;Gupta and Singh, 1989;Shanker et al 2010;Singh et al 2010) have reported changes in seismicity patterns before the occurrence of medium to large earthquakes. Gupta and Singh (1986) observed that it is important to recognise swarm and quiescence before the occurrence of the main shock and made successful prediction of 06 August, 1988 Indo-Burma border earthquake.…”
Section: Precursor and Earthquake Forecastingmentioning
confidence: 99%
“…This is an indication that a possibly wider area will be placed at risk and revised estimates for magnitude and time of occurrence of the mainshock may be necessary. Several authors (Bufe et al, 1974;Sekiya, 1976;Gupta and Singh, 1989;Zheng et al, 1995;Shanker et al, 2010;Singh et al, 2010) have reported changes in seismicity patterns before the occurrence of medium to large earthquakes. Gupta and Singh (1986) observed that it is important to recognise swarm and quiescence before the occurrence of the mainshock and made successful prediction of 06 August, 1988 Indo-Burma border earthquake.…”
Section: Introductionmentioning
confidence: 95%